Comparability of RF-based indoor localisation solutions in heterogeneous environments: an experimental study. (2016) - Haute, Tom Van; Poorter, Eli De; Moerman, Ingrid; Lemic, Filip; Handziski, Vlado; Wolisz, Adam; Wirström, Niklas; Voigt, Thiemo
The growing popularity of indoor localisation research has resulted in a significant amount of research papers describing and evaluating innovative localisation solutions. Unfortunately, the results from most of these research papers cannot easily be compared since they are evaluated in different environments, use different evaluation criteria and typically tailor their solutions towards a single testbed environment. To evaluate how these different conditions influence the localisation performance, in this paper an exhaustive set of experiments has been performed, in which three different localisation solutions have been evaluated using multiple metrics in three different test environments: two types of office environments and an industry-like factory environment. None of the used localisation solutions was previously optimised for any of these test environments and they were all evaluated under similar conditions. The results reveal several weaknesses in the evaluation methods used in the majority of existing scientific literature of indoor localisation solutions.